Effect of Mixed Irrigation of Brackish Water and Reclaimed Water on Soil Ion Exchange Performance - HU Junfang; ZENG Zhi; LIU Chuncheng (Renmin Zhujiang)
The scarcity of fresh water resources limits the utilization of the combination mode of brackish water and fresh water to some extent. To explore new modes of the safe utilization of brackish water, a pot experiment is conducted to study the effects of mixed irrigation of brackish water and reclaimed water on soil exchangeable ions, total exchangeable bases, cation exchange capacity, exchange sodium percentage (ESP), etc. The results indicate that compared to pure irrigation of brackish water, the mixed irrigation of brackish water and reclaimed water in a 1:1 ratio reduces soil exchangeable sodium ion content, soil exchangeable calcium ion content, total exchangeable bases and cation exchange capacity by 59.43%, 9.47%, 24.88% and 20.82%, respectively, while increasing soil exchangeable magnesium and potassium ion contents by 25.94% and 57.89%, respectively. As the proportion of reclaimed water in the liquid mixture increases, soil exchangeable sodium ion content and ESP gradually significantly decrease, while soil exchangeable magnesium ion content shows a trend of significantly increasing. Total exchangeable bases and base saturation show a trend of gradually decreasing. Soil exchangeable sodium ion content, total exchangeable bases and ESP are all extremely significantly positively correlated with soil moisture, salinity, and water drop penetration time (WDPT) (P < 0.01). Additionally, soil exchangeable base saturation is extremely significantly positively correlated with soil moisture and salinity (P < 0.01) after the harvest. Both pH and soil total nitrogen (TN) content are extremely significantly negatively correlated with soil exchangeable sodium ion content, total exchangeable bases and ESP (P < 0.01), and are significantly negatively correlated with soil exchangeable base saturation (P < 0.05). To some extent, the results can provide theoretical reference on new modes of the safe utilization of brackish water.